Examining the Impact of Influencer Endorsements on Consumer Behaviour within the Nutraceutical Industry - Teixeira, Inez (Auckland University of Technology, 2025)
The growing popularity of nutraceutical products, amplified by wellness culture and the COVID-19 pandemic, has been accompanied by the rise of influencer marketing in a largely unregulated digital environment. Despite their perception as safe, natural alternatives to pharmaceuticals, nutraceuticals often lack scientific validation and regulatory oversight, raising concerns about consumer vulnerability and misinformation. This study investigates the impact of influencer endorsements on consumer behaviour in the nutraceutical sector, specifically in comparison to traditional branded advertising. A 2 × 2 between-subjects experimental design was used to assess differences in product evaluations, purchase intent, and perceptions of authenticity, with regulatory awareness and appearance-based consumption motives examined as moderators. Contrary to expectations, branded advertisements outperformed influencer endorsements across all key outcomes. Regulatory awareness significantly weakened the effectiveness of influencer marketing but had minimal effect on branded advertising. Appearance-driven motives consistently predicted favourable product evaluations and heightened purchase intent and further strengthened the influence of source characteristics across both influencer and brand conditions. These findings, informed by psychological frameworks such as the Elaboration Likelihood Model, Social Cognitive Theory, Theory of Planned Behaviour, Parasocial Interaction Theory, and Social Identity Theory, highlight the complex interplay between digital persuasion, consumer identity, and ethical vulnerability. The study offers implications for public policy, marketing practices, and consumer protection in the health and wellness domain.